A theory of wage policy - Dasgupta, A. K. (Delhi : Oxford University Press, 1976)
This book adopts a growth approach as distinct from the industrial relations approach recognizing however that the two are not altogether incompatible.
Includes bibliographical references and index.
ahz 13/03/2019
Loans
Keywords: Wages; Labor policy; Wages and labor productivity